2022
DOI: 10.1111/ijfs.15809
|View full text |Cite
|
Sign up to set email alerts
|

A novel intelligent film with high stability based on chitosan/sodium alginate and coffee peel anthocyanin for monitoring minced beef freshness

Abstract: This study aimed to develop a novel pH-sensitive intelligent film for monitoring minced beef freshness based on chitosan/sodium alginate (CS-SA) and coffee peel anthocyanin (CPA). The different CPA content effects on the internal structure, physical properties and pH sensitivity of the CS-SA films were investigated. The results showed low contents of CPA (≤2%) could be evenly distributed within the CS-SA matrix with good compatibility. The addition of CPA significantly improved the physical properties and pH s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In line with Wu’s study, the addition of red cabbage extract also reduced WVP of pullulan/chitosan/CN film [ 35 ]. However, there was no further decrease for the higher content of 8.75% PSPA, since the aggregation of anthocyanins could destroy the interaction between EC and G, leading to a decrease in compactness and uniformity of the film [ 36 ]. Guo et al found that the WVP of purple cabbage anthocyanins film decreased firstly and then increased with further addition of anthocyanins [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In line with Wu’s study, the addition of red cabbage extract also reduced WVP of pullulan/chitosan/CN film [ 35 ]. However, there was no further decrease for the higher content of 8.75% PSPA, since the aggregation of anthocyanins could destroy the interaction between EC and G, leading to a decrease in compactness and uniformity of the film [ 36 ]. Guo et al found that the WVP of purple cabbage anthocyanins film decreased firstly and then increased with further addition of anthocyanins [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cross sections were observed using a Scanning Electron Microscope (VEGA3; Tesken Co., Ltd., Prague, Czech Republic). The conductive gold layer of about 10 nm was plated on the fracture surface of the film [ 28 ].…”
Section: Methodsmentioning
confidence: 99%